Comparative study of bovine and synthetic hydroxyapatite in micro- and nanosized on osteoblasts action and bone growth. - Maria Apriliani Gani; Gyubok Lee; Chrismawan Ardianto; Fedik Abdul Rantam; Maria Lucia Ardhani Dwi Lestari; Rafi Addimaysqi; I Ketut Adnyana; Kangwon Lee; Junaidi Khotib (PLoS ONE)
Hydroxyapatite (HA) is widely used as a bone graft. However, information on the head-to-head osteoinductivity and in vivo performance of micro- and nanosized natural and synthetic HA is still lacking. Here, we fabricated nanosized bovine HA (nanoBHA) by using a wet ball milling method and compared its in vitro and in vivo performance with microsized BHA, nanosized synthetic HA (nanoHA), and microsized synthetic HA (HA). The results showed that the wet ball milling method successfully reduced the particle size of BHA to 40 nm without changing its natural characteristics. NanoBHA was able to maintain cell viability and induce cell proliferation and calcium deposits. NanoBHA promoted osteogenic differentiation via OPN as a specific regulator, with a 13-fold greater expression level. NanoBHA and HA also activated ERK1/2 indicated corresponding to the proliferation-differentiation and death of cells, respectively. The calvarial bone defect model showed that nanoBHA induced bone growth based on CT images, which is in line with the histological results showing the presence of bone cells and connective tissue at the nanoBHA implantation site. In conclusion, natural HA outperformed synthetic HA. Our findings will attract interest in further research into nanomaterials and their mechanism of action in bone remodeling.